Annual ADEA Survey of Dental School Seniors: 2017 Graduating Class. Issue 5 (1st May 2018) - Wanchek, Tanya; Cook, Bryan J.; Valachovic, Richard W.
Abstract : This report summarizes the key findings of the American Dental Education Association (ADEA) Survey of Dental School Seniors for the graduating class of 2017. The survey covers a wide range of topics related to dental education, including students' motivation to pursue dentistry, perceived preparation in different subject areas, debt incurred, and career plans. The response rate for the survey was 77.1% and included responses from students at all 65 U.S. dental schools with graduating classes that year. Some of the key findings include a near equal representation of males and females, but a skewed distribution by gender within race/ethnic groups. In general, minority students had a higher ratio of females, while White students had a higher ratio of males. Average educational debt fell slightly at public schools but rose by 40, 000 to 287, 405 at private schools. The two most common plans following graduation were to work in the private sector and to continue learning at an advanced dental education program. The majority of students planned at some point in their careers to teach and to work with underserved populations. Comparing the experiences and plans of seniors with different characteristics allows school administrators and policymakers to better understand these future dentists' motivations and challenges.